The Enhancement of Student Career Planning Ability Using Inspirational Class Program in SPANDA TV Virtual Learning Media - Tri Astuti Yuliandari (Teknodika, 2021)
This study aims to 1) improve students' career planning skills using inspirational class programs and 2) know the process of career guidance and counseling services using inspirational class programs on SPANDA TV virtual learning media. The type of research used was classroom action research with Kemmis and Mc. Taggart’s model. The inspirational class program is a modeling method in guidance and counseling services by bringing in several resource persons to be used as role models in career planning, but it was implemented virtually through SPANDA TV virtual learning media. This program's use could improve students' career planning skills on several indicators, including self-assessment ability, ability to read career opportunities (exploring opportunities), ability to make decisions and determine goals, planning ability, and the ability to pursue career goals (pursuit of achievement). The improvement of students' career planning abilities could be seen from the aspects of interest in participating in the inspirational class program, aspects of the success of making career mind-mapping, and aspects of increasing the mean score of the career planning scale before action (101.8 in the moderate category) to 106.7 (high category) in cycle I, and increased significantly to 109.3 (high category) in cycle II.